Farmacoepidemiologia e farmacoeconomia della terapia anti-ipertensiva: uno studio osservazionale della popolazione della Asl di Ravenna - Degli Esposti, Luca; Capone, Alessandro; Di Martino, Mirko; Saragoni, Stefania; Berlini, Samuele; Russo, Pierluigi; Degli Esposti, Ezio (Farmeconomia. Health Economics and Therapeutic Pathways, 2003)
The aim of the paper was to perform a pharmacoepidemiological and pharmacoeconomic analysis ofantihypertensive drug treatment. An administrative database kept by the Local Health Unit of Ravenna listing patient baseline characteristics, drug prescriptions and hospital admissions was used to perform a population-based cohort study. The study included all new users of antihypertensive drugs, 20 years of age or over receiving a first prescription for diuretics, beta-blockers, calcium channel-blockers, ACE inhibitors or angiotensin II antagonists (AIIAs) between January 1st, 2000 and December 31st, 2000. All prescriptions for anti-hypertensive drugs filled during the 12-months follow-up period were considered. Patients were classified as continuers, switchers and discontinuers on the basis of their prescription dynamics. A total of 14.062 patients were included in the study of whom only 39,7% resulted persistent at 12 months. Patients initially prescribed for AIIAs were more likely to continue antihypertensive treatment than those started on other drug classes as well as those with older age, concurrent drug therapies and previous hospitalisation for cardiovascular diseases. The overall cost of the study cohort for antihypertensive drugs amounted to 1.238.752,37 euros of which 80,6% was used for persistent patients. The annual average cost for antihypertensive drugs was 171,73 euro for continuers, 205,10 euros for switchers and 28,29 euros for discontinuers. Factors associated to drug cost were age, pattern of persistence, number of prescribed drug classes, and class prescribed at enrolment. Nonpersistence with antihypertensive pharmacotherapy induced a high cost for the consumption of antihypertensive drug since discontinuers are responsible for a significant percentage of drug resources allocated on subjects exposed to therapy. A correlation between drug therapy cost and persistence with treatment is needed to evaluate the appropriateness of drug utilization and to perform cost-effectiveness analyses between alternative pharmacological agents.